Eksistensi Tradisi Tale Naek Joi Di Desa Permanti Kecamatan Pondok Tinggi Kota Sungai Penuh - Nega Lezer, Apras (Krinok: Jurnal Pendidikan Sejarah dan Sejarah, 2024)
This research focuses on the existence of the tale naek joi tradition in permanti village and how it is implemented in terms of time method. This research uses a qualitative descriptive research method with a research focus on obtaining accurate and comprehensive data and information. This tradition, known as a tale joi, has a become inseparable part of the way of life of the Kerinci people, it also functions as a regional identity and is part of the traditionalist movement of the people in the Permanti village area, Pondok Tinggi Sungai Penuh city. Even though the world is becoming more sophisticated and developing, the Permanti people still consistenly carry out the tale tradition for perspective hajj pilgrims who will eventually depart for the holy land.